Bayesian inference for economic agent-based models - Platt, D (2021)
Interest in agent-based models of financial markets and the wider economy has increased consistently over the last few decades, in no small part due to their ability to reproduce a number of empirically-observed stylised facts that are not easily recovered by more traditional modelling approaches. Nevertheless, the economic agent-based modelling paradigm faces mounting criticism, focused particularly on the rigour of current validation, calibration, and model selection practices, which still, in many cases, remain qualitative and stylised fact-driven. While the literature on quantitative and data-driven approaches has seen significant expansion in recent years, many studies have focused on the introduction of new methods that are neither benchmarked against existing alternatives nor rigorously tested on the large-scale and computationally-expensive variants that now dominate the literature, instead choosing to focus on highly-simplified models that are no longer representative of the current state of the art. This has ultimately led to some doubt regarding the applicability of current approaches to the kinds of problems of interest to most contemporary modellers and policymakers.